17. THE OPTiMISE STUDY: AMISULPRIDE AND OLANZAPINE FOLLOWED BY OPEN-LABEL TREATMENT WITH CLOZAPINE IN FIRST-EPISODE SCHIZOPHRENIA - Arango, Celso (Schizophrenia bulletin, 2019)
Abstract No accepted treatment algorithm exists for patients with first episode schizophrenia. Whether switching antipsychotics, how long to wait for a response, or if early use of clozapine improves out-come in first-episode schizophrenia is unknown. The OPTiMISE study assessed 481 first episode schizophrenia patients using three phase switching study. Patients with a first episode of schizophrenia entered a four-week open treatment with amisulpride. Those patients who did not achieved remission entered a 6-week, randomized, double-blind study of either continuation of amisulpride or switching to olanzapine. Those patients who still not achieved remission were treated with clozapine for 12-weeks in an open study design. Levi et al will present data on predictors of relapse after the first psychotic episode. Multivariate analyses showed significant effects on relapse only for cannabis use (OR=2.011, 95% CI:1.024–4.087, p=0.021). Studies should investigate the effect of cannabis cessation programs on relapse rates. Armida et al will present the prevalence of negative symptoms of moderate severity, unconfound-ed by depression and extrapyramidal symptoms at baseline (U-NEG), and their persistence over the three phases of the OPTIMISE trial (i.e., after 4, 10 and 22 weeks of treatment). The impact on re-mission and psychosocial functioning of persistent negative symptoms (PNS) was also assessed. U-NEG were observed in 263/446 subjects (59% of the whole cohort of first-episode, recent-onset subjects Unconfounded negative symptoms predicted poor psychosocial functioning. Persistent negative symptoms were associated with the worse psychosocial functioning at all phases and were the most resistant to antipsychotic treatment including clozapine. Baandrup et al evaluated the scalability of the PANSS negative symptom subscale using Rasch (or IRT) analysis. They found that the negative symptom subscale does not possess the necessary properties to be a valid rating scale. However, the individual negative symptom items possess better scalability and seem better suited for future research in negative symptoms. Finally, Glaichenhaus et al will present data supporting that serum level of some cytokines combined with clinical subtypes (based on a hierarchical clustering approach using the PANSS) predict remission. The predictive value of this model was 73%,